Outcomes of conservatively managed coracoid fractures in wild birds in the United Kingdom - Cracknell, Jonathan M.; Lawrie, Alistair M.; Yon, Lisa; Hopper, Jane S.; Pereira, Yolanda Martinez; Smaller, Eve (Association of Avian Veterinarians, 2018)
Coracoid fractures are a frequent presentation in wild birds, commonly due to collisions with motor vehicles, windows, or other obstacles such as pylons. Despite this, there are few literature reports of outcomes, and those published consist of small numbers of animals, with conflicting results when comparing conservative management with surgical intervention. Outcomes of 232 adult wild birds in the United Kingdom (UK), surviving more than 48 hours after admission, with only closed unilateral coracoid fractures confirmed on radiography were retrospectively analysed. There was a high success rate for conservative management, with 75% (95% confidence interval of 69-80%, n=174/232) of all birds successfully released back to the wild. The proportion of raptors successfully returned to the wild was even higher at 97% (95% CI 85-99%, n=34/35). A statistically significant difference of 26% (95% CI of 18-34%, Fishers exact test p<0.001, Z=6.08) was demonstrated, when comparing the raptor outcomes (97% success, n=34/35) to the non-raptor outcomes (71%, n=140/198). The median time in captive care until released back to the wild was 30 days (95% CI 27-33 days). Conservative management of coracoid fractures in wild birds in the UK, and in particular in raptors, appears to result in good outcomes. The approach is low cost and non-invasive, in contrast to surgery, and is recommended as the first line approach of choice in these cases.